Analysis of Physical Environmental Factors Affecting the Incidence of Pulmonary Tuberculosis in Magelang City - Preztiana, Arnies Mega; Raharjo, Bambang Budi; Wijayanti, Yuni (Universitas Negeri Semarang, 2022)
Efforts to improve public health are based on community participation in overcoming the environment because the environment is one of the factors that play a role in the emergence of a disease. In 2015, the Central Java government determined the most located area in Pemalang Regency which was later determined by a Regent's Decree. There are four sub-districts in the Pemalang Regency area which are included in the category that does not have latrines, namely Pemalang, Taman, Petarukan, and Comal sub-districts.The purpose of the study was to analyze the factors that influence community participation in the construction of family latrines in Petarukan District, Pemalang Regency. This study used a cross sectional design. The sampling technique is proportional stratified simple random sampling. The population is 3,882 households in 3 urban village/village, while the sample is 100. The instrument uses a questionnaire sheet. Data were analyzed by univariate, bivariate with Chi Square and multivariate with logistic regression. The results of the Chi square test show that knowledge factors that influence participation in latrine construction are age (p = 0.02), education (p = 0.01), income (p = 0.00), and (p = 0.00) . The results of the logistic regression showed that the factors that had the most influence on community participation in latrine construction were the level of knowledge.